2011 Chinese Control and Decision Conference (CCDC) 2011
DOI: 10.1109/ccdc.2011.5968799
|View full text |Cite
|
Sign up to set email alerts
|

Moment stability in mean square of stochastic delay differential equation

Abstract: Abstract-In this paper, we derive a moment stability region in terms of coefficient parameters for a stochastic delay differential equation. Such a stochastic delay equation with both time delay and random effects is an essential model of control systems. As a main result, a fundamental stability problem is solved by delay-dependent stochastic analysis. We adopt the domain-subdivision approach and use Ito's formula in the analysis. For a given time delay, the stability of the stochastic delay differential equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In [7] and [8], the authors also showed that the influence of time delay can be reduced by noise for a scalar stochastic delay system with particular parameters. They used the so-called domain subdivision approach [9] together with the Ito's formula to derive the stability regions in terms of the parameters of a given equation and to deal with the fluctuation noise.…”
Section: Introductionmentioning
confidence: 99%
“…In [7] and [8], the authors also showed that the influence of time delay can be reduced by noise for a scalar stochastic delay system with particular parameters. They used the so-called domain subdivision approach [9] together with the Ito's formula to derive the stability regions in terms of the parameters of a given equation and to deal with the fluctuation noise.…”
Section: Introductionmentioning
confidence: 99%
“…For an end-fixed inverted pendulum, it was shown that stability is enhanced by the existence of noise with appropriate power [3]. The authors showed that the influence of time delay can be reduced by noise for a scalar stochastic delay system [4,5].…”
Section: Introductionmentioning
confidence: 99%